Negative active material and preparation method thereof, negative pole piece and secondary battery

By using porous graphene and molybdenum disulfide composite materials as the negative electrode active material of lithium-ion batteries, the problem of poor negative electrode kinetic characteristics is solved, high specific capacity and rate performance are achieved, and the service life of the battery is extended.

CN119864393APending Publication Date: 2025-04-22BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411973212.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

During the charging process, lithium-ion batteries have poor negative electrode dynamic characteristics, which may cause lithium degradation of the negative electrode, affecting the battery life and limiting the charging rate of the secondary battery.

Method used

Porous graphene and molybdenum disulfide composite material loaded thereon are used as the negative electrode active material. By combining the layered crystal structure of molybdenum disulfide with the high conductivity of graphene, electron transfer rate and lithium ion embedding and removal ability are improved, and specific surface area is increased to achieve high specific capacity and rate performance.

Benefits of technology

It realizes the rapid shuttle and efficient embedding and disengagement of lithium ions, improves the capacity and rate performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864393A_ABST
    Figure CN119864393A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries. The invention provides a negative electrode active material and a preparation method thereof, a negative electrode plate and a secondary battery, the negative electrode active material comprises porous graphene and molybdenum disulfide loaded on the porous graphene, and the specific surface area of the negative electrode active material is 600m < 2 > / g-1800m < 2 > / g. The negative electrode active material provided by the invention has more active sites and high electronic conductivity, can realize rapid shuttle of lithium ions in a negative electrode to the active material, is high in reaction rate, and realizes high specific capacity and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode plate and a secondary battery. Background Art

[0002] As secondary batteries are gaining more and more attention, faster charging modes have become the demand of most consumers. However, due to the characteristics of lithium-ion batteries, due to the poor kinetic characteristics of the negative electrode during charging, excessive charging rates may cause lithium deposition at the negative electrode, affecting the service life of the power battery. Therefore, the slower charging rate still affects the consumer experience and has become an important factor restricting the development of secondary batteries. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a negative electrode active material, the negative electrode active material provided by the present invention has high specific capacity, and the battery containing the negative electrode active material has excellent rate performance.

[0004] To this end, the first aspect of the present invention provides a negative electrode active material, the negative electrode active material comprises porous graphene and molybdenum disulfide supported on the porous graphene, and the specific surface area of ​​the negative electrode active material is 600m 2 / g-1800m 2 / g.

[0005] The negative electrode active material proposed in the present invention combines molybdenum disulfide and graphene to combine the layered crystal structure of molybdenum disulfide with the high conductivity of graphene. Graphene can increase the conductivity of the material and improve the electron transmission rate. The material has a three-dimensional network structure, which is conducive to the rapid transmission of lithium ions in the pores of the material, while the van der Waals interaction between the molybdenum disulfide layers is conducive to the insertion and extraction of ions, thereby improving the specific capacity of lithium ions. In addition, the specific surface area of ​​the negative electrode active material is 600m 2 / g-1800m 2 / g, which enables lithium ions to quickly shuttle in the negative electrode to reach the active material. At the same time, it has high electronic conductivity and fast reaction rate, achieving high specific capacity and rate performance.

[0006] In some embodiments of the present invention, the specific surface area of ​​the negative electrode active material is 800 m 2 / g-1200m 2 / g.

[0007] In some embodiments of the present invention, the mass ratio of the porous graphene to the molybdenum disulfide is (1-2): (1-2); and / or the molybdenum disulfide is a two-dimensional layered structure with 3 to 15 layers.

[0008] In a second aspect of the present invention, the present invention provides a method for preparing the negative electrode active material according to the first aspect, comprising:

[0009] Providing a substrate, wherein the porosity of the substrate is 70%-95%;

[0010] Generating graphene on the substrate by chemical vapor deposition to obtain graphene containing the substrate material;

[0011] Adding glue to the graphene containing the substrate material, spreading the glue, and drying the graphene so that at least part of the gaps in the graphene are filled with the filling glue to obtain a first intermediate;

[0012] Removing the substrate material from the intermediate, and placing the intermediate in an aqueous solution containing a soluble molybdenum source and a soluble sulfur source for hydrothermal reaction to obtain a second intermediate;

[0013] The filler is removed to obtain the negative electrode active material.

[0014] Through the above method, a composite material of molybdenum disulfide and graphene can be prepared, and the two can be evenly compounded, and the specific surface area of ​​the negative electrode active material is 600m 2 / g-1800m 2 / g, has more active sites, and has high electronic conductivity, which can enable lithium ions to quickly shuttle in the negative electrode to reach the active material, with a fast reaction rate, achieving high specific capacity and rate performance.

[0015] In some embodiments of the present invention, the porosity of the substrate is 85%-95%; and / or the substrate includes at least one of foamed nickel, foamed molybdenum, and foamed copper; and / or, before depositing the graphene, the substrate is first treated by the following method: the substrate is cleaned with ketone, alcohol, acid and water in sequence, annealed at 600°C-1200°C for 20min-60min in a hydrogen and argon atmosphere, and cooled.

[0016] In some embodiments of the present invention, the glue comprises a polymer and a solvent, the mass ratio of the polymer to the solvent is 1:(10-30), preferably 1:(15-25); and / or the polymer comprises at least one of polymethyl methacrylate, methyl methacrylate-styrene copolymer, and styrene-methacrylic acid copolymer; and / or the solvent comprises anisole.

[0017] In some embodiments of the present invention, the intermediate is soaked in hydrochloric acid to remove the substrate material in the intermediate; and / or the temperature of the hydrothermal reaction is 120°C-200°C, preferably 150°C-180°C; and / or the time of the hydrothermal reaction is 6h-18h, preferably 8h-16h; and / or the molybdenum source includes sodium molybdate, and the concentration of sodium molybdate in the aqueous solution containing a soluble molybdenum source and a soluble sulfur source is 0.5g / L-4.0g / L, preferably 1.0g / L-3.0g / L.

[0018] In some embodiments of the present invention, removing the filler to obtain the negative electrode active material comprises: soaking the second intermediate in acetone for 20 min to 60 min, and freeze-drying to obtain the negative electrode active material.

[0019] In the third aspect of the present invention, the present invention provides a negative electrode plate, comprising the positive electrode active material described in the first aspect of the present invention, or the negative electrode active material prepared by the method described in the second aspect.

[0020] In a fourth aspect of the present invention, the present invention provides a secondary battery, comprising the negative electrode plate described in the third aspect of the present invention, whereby the battery provided by the present invention has excellent capacity and rate performance.

[0021] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings, in which:

[0023] Figure 1 This is a SEM image of the negative electrode active material prepared in Example 1 of the present invention.

[0024] Figure 2 This is another SEM image of the negative electrode active material prepared in Example 1 of the present invention.

[0025] Figure 3 This is a TEM image of the negative electrode active material prepared in Example 1 of the present invention.

[0026] Figure 4 This is the HRTEM image of the negative electrode active material prepared in Example 1 of the present invention.

[0027] Figure 5 This is the XRD pattern of the negative electrode active material prepared in Example 1 of the present invention.

[0028] Figure 6It is a 100 mAh / g cycle 80-week trend chart of the batteries of Examples 1-3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0029] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0030] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0031] In a first aspect of the present invention, the present invention provides a negative electrode active material, the negative electrode active material comprises porous graphene and molybdenum disulfide supported on the porous graphene, and the specific surface area of ​​the negative electrode active material is 600m 2 / g-1800m 2 / g.

[0032] For example, the specific surface area of ​​the negative electrode active material can be 600 m 2 / g,800m 2 / g,1000m 2 / g,1500m 2 / g,1800m 2 / g, etc.

[0033] Correspondingly, the porosity of the negative electrode active material is 70%-95%. In some other embodiments of the present invention, the porosity of the negative electrode active material is 85%-95%.

[0034] The negative electrode active material proposed in the present invention combines molybdenum disulfide and graphene, and can combine the layered crystal structure of molybdenum disulfide with the high conductivity of graphene. Graphene can increase the conductivity of the material and improve the electron transmission rate. The porous material has a three-dimensional network structure, which is conducive to the rapid transmission of lithium ions in the pores of the material, and the van der Waals interaction force between the molybdenum disulfide layers is conducive to the embedding and extraction of ions, thereby improving the specific capacity of lithium ions. In addition, the porosity of the negative electrode active material is as high as 70%-95%, which can realize the rapid shuttle of lithium ions in the negative electrode to reach the active material. At the same time, it has high electronic conductivity and fast reaction rate, and achieves high specific capacity and rate performance.

[0035] The carbon atoms in porous graphene are hybridized into sp2 hybridization, forming a two-dimensional planar structure, in which each carbon atom forms a six-membered aromatic hydrocarbon structure, and the central part is a special π electron conjugated system. Since sp2 hybridization and π electron conjugation reflect the excellence of the electron orbit of carbon atoms, graphene has high conductivity. Due to the conjugation of the π electron orbit in graphene, each carbon atom can be connected to each other to form a pair of electrons, thus forming a conjugated π electron system. These π electrons form an electric domain in the lattice with high conductivity. The carbon atoms in graphene are arranged very regularly and in long-range order (each carbon atom has a strong covalent bond with its adjacent carbon atoms), and the electrons are transferred at high speed, making the electron flow very smooth and having very high conductivity.

[0036] Molybdenum disulfide is a quasi-two-dimensional layered structure, showing a typical three-layer structure, with a Mo metal layer in the middle and two S layers above and below, that is, a Mo layer is sandwiched between two S layers, and the c-axis spacing of the metal sulfide crystal structure is 0.6nm. In the crystal structure, there is a large interlayer spacing in the c-axis direction, which is suitable for the embedding of lithium ions and sodium ions. There is a covalent bond between Mo-S, and the adjacent layers are connected by van der Waals force. In this way, a special structure with extremely strong intra-layer action and relatively weak inter-layer bonding is formed. This feature can be used as an embedded electrode material for electrochemical lithium storage. There are many gaps inside the layered structure of molybdenum disulfide, and it has good electrical conductivity. It can quickly insert and remove lithium, has a high lithium ion insertion and extraction capacity, and can achieve efficient utilization of energy storage. Its theoretical capacity is as high as 670mAh / g, which is higher than the 372mAh / g of graphite negative electrode materials. The use of molybdenum disulfide can improve the energy density of the battery, achieve longer battery life and higher energy output, but the conductivity of molybdenum disulfide needs to be improved, and porous graphene has a very large specific surface area and high conductivity. The larger specific surface area can increase the contact between the negative electrode active material and the electrolyte. The graphene surface has more disordered structures and edge defect structures, has a higher lithium storage capacity, and has significantly better rate performance than graphite. The high ductility of graphene can prevent the agglomeration and crushing of active particles during the cycle. While serving as a conductive matrix, graphene can evenly distribute nanoparticles on its surface and buffer the deformation stress generated by nanoparticles during the charge and discharge process. As a negative electrode material for lithium-ion batteries, disulfide graphene composites have high specific capacity, excellent rate charging performance, and stable cycle stability.

[0037] In some embodiments of the present invention, the mass ratio of the porous graphene to the molybdenum disulfide is (1-2): (1-2). For example, the mass ratio of the two can be 1:1, 1:1.5, 1:2, 2:1, etc. Controlling the mass ratio of the porous graphene to the molybdenum disulfide within the above range is conducive to the rapid transmission of lithium ions in the pores of the material, while the van der Waals interaction between the molybdenum disulfide layers is conducive to the insertion and extraction of ions, thereby increasing the specific capacity of lithium ions. In addition, the specific surface area of ​​the negative electrode active material is 600-1800m 2 / g, has more active sites, and has high electronic conductivity, which can enable lithium ions to quickly shuttle in the negative electrode to reach the active material, with a fast reaction rate, achieving high specific capacity and rate performance.

[0038] In some embodiments of the present invention, the specific surface area of ​​the negative electrode active material is 800-1200 m 2 / g, for example, it can be 800m 2 / g,900m 2 / g,1000m 2 / g,1100m 2 / g,1200m 2 / g, etc., thus, the negative electrode active material has a large specific surface area, which can increase the contact area between the negative electrode active material and the electrolyte, which is beneficial to the rapid transmission of lithium ions in the pores of the material and improves the capacity and rate performance of the battery containing it.

[0039] In some embodiments of the present invention, the molybdenum disulfide is a two-dimensional layered structure with 3 to 15 layers, for example, 3 layers, 5 layers, 7 layers, 9 layers, 10 layers, 15 layers, etc. The number of microscopic layers of molybdenum disulfide is controlled within the above range, so that the negative electrode active material has a very high lithium ion embedding and extraction capacity, achieving high specific capacity and rate performance.

[0040] In a second aspect of the present invention, the present invention provides a method for preparing the negative electrode active material according to the first aspect, comprising:

[0041] S1. providing a substrate, wherein the porosity of the substrate is 70%-95%;

[0042] As an example, the porosity of the substrate may be 70%, 75%, 80%, 85%, 90%, 95%, etc. In other embodiments of the present invention, the porosity of the substrate is 85%-95%.

[0043] The substrate has a high porosity and can be used as a template to deposit graphene thereon, thereby increasing the porosity of the deposited graphene and further increasing the porosity of the negative electrode active material.

[0044] In some embodiments of the present invention, the substrate includes at least one of nickel foam, molybdenum foam, and copper foam. The above materials have high porosity, and when graphene is deposited thereon, porous graphene can be formed, and it is easy to separate from the porous graphene later.

[0045] In some embodiments of the present invention, before step S1, the method further includes:

[0046] S0. Clean the substrate with ketone, alcohol, acid and water in sequence, anneal at 600° C.-1200° C. for 20 min-60 min in a hydrogen and argon atmosphere, and cool.

[0047] Specifically, acetone, anhydrous ethanol, and hydrochloric acid are used to remove oxides and impurities on the surfaces of metal substrates such as foamed nickel, foamed molybdenum, and foamed copper, and then the substrates are cleaned with deionized water and vacuum dried.

[0048] The cleaned and dried substrate is subjected to vacuum high-temperature annealing in a tube furnace, and hydrogen and argon gases are introduced to remove residual oxides on the surface of the metal substrate and increase the size of the metal grains.

[0049] As an example, the annealing temperature may be 600° C., 800° C., 1000° C., 1200° C., etc. In other embodiments, the annealing temperature is 800-1100° C.

[0050] The annealing time may be 20 min, 30 min, 40 min, 50 min, 60 min, etc. In other embodiments, the annealing time is 30 to 40 min.

[0051] S2. Using chemical vapor deposition method, graphene is generated on the substrate to obtain graphene containing substrate material.

[0052] This step uses chemical vapor deposition to deposit graphene. Chemical vapor deposition makes the graphene have an excellent lattice structure, a small amount of defects and impurities, and a high porosity and specific surface area. It can improve the purity, porosity and specific surface area of ​​the obtained negative electrode active material, thereby improving the capacity and rate performance of the battery.

[0053] In some embodiments of the present invention, the substrate after cleaning and annealing is placed in a chemical vapor deposition device, the temperature is raised to 700-1300°C (for example, it can be 700°C, 900°C, 100°C, 1200°C, 1300°C, etc., and the preferred temperature is 800-1200°C), methane, hydrogen, and argon are introduced, and after the flow rates of hydrogen, argon and methane tend to be stable, the heating is stopped at the same time, and the temperature is maintained at 700-1300°C (for example, it can be 700°C, 900°C, 100°C, 1200°C, 1300°C, etc., and the preferred temperature is 800-1200°C) for 5-10 min (for example, it can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc., and the preferred time is 6-8 min) to grow graphene.

[0054] Then cool down. When the temperature in the chemical vapor deposition device drops to about 300-600°C (for example, it can be 300°C, 400°C, 500°C, 600°C, etc.), open the argon valve to adjust the flow, cut off the source of hydrogen and argon, and drop to room temperature under the protection of argon. Turn off the argon and vacuum pump, open the valve to take out the grown graphene foam nickel, foam molybdenum, and foam copper.

[0055] S3, adding glue to the graphene containing the substrate material, spreading the glue, and drying, so that at least part of the gaps in the graphene are filled with the filling glue, to obtain a first intermediate;

[0056] By adding glue and leveling glue, a protective layer can be formed on the surface and in the pores of graphene, which not only reduces the damage that may be caused to graphene in subsequent operations, but also avoids excessive corrosion or structural destruction of graphene during chemical treatment, maintaining the structural integrity of graphene. At the same time, the filling glue acts as a physical support to prevent the closed-pore phenomenon of microporous three-dimensional graphene pores and maintain the high specific surface area and porosity of graphene. In addition, the chemical or physical interaction formed by the polymer in the glue and graphene further enhances the overall stability of the three-dimensional microporous graphene, reduces the direct contact between graphene sheets, thereby reducing agglomeration and maintaining the structural integrity and performance of the microporous three-dimensional graphene.

[0057] In some embodiments of the present invention, the glue includes a polymer and a solvent, and the mass ratio of the polymer to the solvent is 1: (10-30), preferably 1: (15-25). For example, the mass ratio of the two can be 1: 10, 1: 20, 1: 30, etc. Controlling the mass ratio of the two within the above range can further protect the integrity of the graphene structure, improve the capacity of the prepared negative electrode active material, and improve the rate performance of the battery.

[0058] In some embodiments of the present invention, the polymer includes at least one of polymethyl methacrylate, methyl methacrylate-styrene copolymer, and styrene-methacrylic acid copolymer. The above polymers have strong stability and can well protect the integrity of the graphene structure, thereby improving the capacity of the prepared negative electrode active material and the rate performance of the battery.

[0059] In some embodiments of the present invention, the solvent includes anisole. The above solvent may volatilize during drying.

[0060] In some embodiments of the present invention, the integrity of the graphene structure is protected by glue preparation and homogenization. A magnetic stirrer stirs the polymer and solvent mixture at a stirring speed of 50 to 200 rpm (for example, 50 rpm, 100 rpm, 150 rpm, 200 rpm, etc., preferably 80 to 120 rpm), and is set aside after clarification. After the graphene containing the substrate material is dripped, homogenization begins, and the sample after homogenization is vacuum dried at a temperature of 30 to 70°C (for example, 30°C, 40°C, 50°C, 60°C, 70°C, etc., preferably 40 to 60°C) for 4 to 8 hours.

[0061] S4, removing the substrate material in the intermediate, and placing it in an aqueous solution containing a soluble molybdenum source and a soluble sulfur source for hydrothermal reaction to obtain a second intermediate.

[0062] Through hydrothermal reaction, two-dimensional nano disulfide can be grown on a three-dimensional network structure of thin-layer graphene. This material has a high porosity, which enables lithium ions to quickly shuttle in the electrode to reach the active material. It also has high electronic conductivity and a fast reaction rate, achieving high specific capacity and rate performance.

[0063] In some embodiments of the present invention, a certain amount of 4-10 mol / L (for example, 4 mol / L, 5 mol / L, 7 mol / L, 9 mol / L, 10 mol / L, etc., preferably a concentration of 6-8 mol / L) of hydrochloric acid is added to a beaker containing an intermediate sample from which the substrate material has been removed, and the sample is heated at 60°C to 120°C (for example, 60°C, 70°C, 90°C, 110°C, 120°C, etc., preferably at a temperature of 80-100°C) for 4 hours, and then the sample is dried in a freeze dryer for 24 hours to prevent graphene collapse.

[0064] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 120°C-200°C, preferably 150°C-180°C, for example, it can be 120°C, 140°C, 160°C, 180°C, 200°C, etc. The temperature of the hydrothermal reaction is controlled within the above range. The hydrothermal reaction temperature is relatively low, so that the formation of molybdenum disulfide is time-effective, and nano-molybdenum disulfide with good morphology can be obtained, which is convenient for generating two-dimensional nano-molybdenum disulfide with a large specific surface area, and can realize the rapid shuttle of lithium ions in the electrode to reach the active material. At the same time, it has high electronic conductivity and fast reaction rate, and achieves high specific capacity and rate performance.

[0065] In some embodiments of the present invention, the hydrothermal reaction time is 6h-18h, preferably 8h-16h. For example, the hydrothermal reaction time can be 6h, 8h, 10h, 15h, 18h, etc. The hydrothermal reaction time is controlled within the above range. The hydrothermal reaction time is short, so that the formation of molybdenum disulfide is time-effective, and nano-molybdenum disulfide with good morphology can be obtained, which is convenient for the generation of two-dimensional nano-molybdenum disulfide with a large specific surface area, and can realize the rapid shuttle of lithium ions in the electrode to reach the active material. At the same time, it has high electronic conductivity and fast reaction rate, and achieves high specific capacity and rate performance.

[0066] In some embodiments of the present invention, the molybdenum source includes sodium molybdate, and the concentration of sodium molybdate in the aqueous solution containing a soluble molybdenum source and a soluble sulfur source is 0.5g / L-4.0g / L, preferably 1.0g / L-3.0g / L. For example, it can be 0.5g / L, 1g / L, 2g / L, 3g / L, 4g / L, etc. By controlling the concentration of sodium molybdate within the above range, nano-molybdenum disulfide with good morphology can be obtained, which is convenient for generating two-dimensional nano-molybdenum disulfide with a large specific surface area, and can realize rapid shuttle of lithium ions in the electrode to reach the active material, and at the same time has high electronic conductivity, fast reaction rate, and high specific capacity and rate performance.

[0067] S5, removing the filler to obtain a negative electrode active material.

[0068] In some embodiments of the present invention, step S5 comprises:

[0069] S51, soaking the second intermediate in acetone for 20 min-60 min, and freeze-drying to obtain a negative electrode active material.

[0070] For example, the immersion treatment time can be 20 min, 30 min, 40 min, 50 min, 60 min, etc. Controlling the immersion time within the above range is sufficient to remove the filler in the negative electrode active material and obtain a negative electrode active material with high porosity, which can enable lithium ions to quickly shuttle in the negative electrode to reach the active material. At the same time, it has high electronic conductivity and fast reaction rate, achieving high specific capacity and rate performance.

[0071] In summary, the present invention firstly removes impurities and residual oxides on the surface of the metal substrate through pretreatment and increases the size of the metal grains. By adding glue and leveling glue, the integrity of the graphene structure can be protected to avoid damage to the graphene caused by subsequent operations. Then, the chemical vapor deposition method is used to make the graphene have an excellent lattice structure, a small amount of defects and impurities, and a high porosity and specific surface area. The heating temperature is low and the heat preservation and pressure holding time is short during the preparation process by the hydrothermal method, which has time effectiveness. Finally, the filling glue is removed to obtain the negative electrode active material. The obtained negative electrode active material has high porosity, large specific surface area, and a nanosheet morphology. The nanosheets are interconnected. This morphology makes it easier for the electrolyte to infiltrate, which is conducive to the rapid transmission of lithium ions, and achieves high specific capacity and rate performance.

[0072] In the third aspect of the present invention, the present invention provides a negative electrode plate, comprising the positive electrode active material described in the first aspect of the present invention, or the negative electrode active material prepared by the method described in the second aspect. Thus, the secondary battery containing the negative electrode plate of the present invention has excellent capacity and rate performance.

[0073] In a fourth aspect of the present invention, the present invention provides a secondary battery, comprising the negative electrode plate described in the third aspect of the present invention, whereby the battery provided by the present invention has excellent capacity and rate performance.

[0074] It can be understood that the negative electrode plate of the third aspect and the battery of the fourth aspect of the embodiment of the present invention have all the beneficial effects of the negative electrode active material described in the first aspect and the method described in the second aspect, which will not be described one by one here.

[0075] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.

[0076] Example 1

[0077] (1) Use acetone, anhydrous ethanol, and hydrochloric acid to remove oxides and impurities on the surface of nickel foam with a diameter of 15 mm, wash with deionized water, and then vacuum dry.

[0078] (2) The treated metal substrate is annealed at 1000° C. for 30 min in a vacuum tube furnace by introducing 8 sccm of hydrogen and 100 sccm of argon to remove residual oxides on the surface of the metal substrate and increase the size of metal grains.

[0079] (3) While the temperature is rising, 2 sccm of methane is turned on. After the hydrogen, argon and methane are stable, the temperature is stabilized at 1100°C. After maintaining for 8 minutes, the graphene growth process is completed, and the methane is turned off and the temperature is turned off to cool down.

[0080] (4) When the temperature drops to about 400°C, turn off the hydrogen gas, and lower it to room temperature under the protection of argon gas. Turn off the vacuum pump and argon gas, let in air, open the valve and take out the nickel foam with grown graphene.

[0081] (5) Mix polymethyl methacrylate and anisole in a mass ratio of 1:20, stir the mixed liquid with a magnetic stirrer until it is clear, then add a small amount of glue to the graphene foam nickel sample and vacuum dry it at 60°C for 6h.

[0082] (6) The sample was immersed in 6 mol / L hydrochloric acid and heated to 80° C. for 4 hours to remove the metallic nickel. The sample was then vacuum dried at −20° C. for 16 hours to obtain a graphene material.

[0083] (7) Weigh 20 mg of sodium molybdate and 40 mg of thioacetamide, dissolve them in deionized water, the concentration of sodium molybdate in deionized water is 1.5 g / L, put the graphene material into the solution, and heat it in a reactor at 160° C. for 8 hours.

[0084] (8) The sample was taken out and washed with deionized water, soaked in acetone for 30 min to remove the filler, and vacuum dried at -20 °C for 16 h to finally obtain a molybdenum disulfide / graphene composite negative electrode active material.

[0085] The mass ratio of graphene material to molybdenum disulfide is 1:1.

[0086] The negative electrode active material prepared in Example 1 was subjected to SEM (scanning electron microscopy), TEM (transmission electron microscopy), HRTEM (high-resolution transmission electron microscopy) and XRD (X-ray diffraction) tests. Figure 1-5 shown. Figure 1 It can be seen that it is a three-dimensional network structure, and molybdenum disulfide is evenly attached to the surface of graphene. Figure 2 MoS2 is shown clustered together in layers. Figure 3 The large flakes shown in the figure are graphene, and the small flakes are molybdenum disulfide. Figure 4 The interlayer spacing of molybdenum disulfide is shown to be 0.62 mm. Figure 5 It can be seen from the XRD diagram that the negative electrode active material obtained in Example 1 has a good crystal structure, which is beneficial to the capacity and cycle performance.

[0087] Examples 2-9 and Comparative Examples 1-2 are the same as Example 1, except that the processes for preparing the negative electrode active materials are different, as shown in Table 1.

[0088] Compared with Example 1, Comparative Example 1 does not perform steps (7) and (8), and directly uses the prepared graphene material as the negative electrode active material. Comparative Example 2 only performs step (7) and does not add graphene material in step (7), and only obtains molybdenum disulfide as the negative electrode active material.

[0089] Table 1

[0090]

[0091] The negative electrode active materials obtained in Examples 1-9 and Comparative Examples 1-2 were used as electrode materials for buckle half-cells, 16 mm lithium sheets were used as counter electrodes, 18 mm polypropylene was used as isolation membranes, and 1 M lithium hexafluorophosphate was dissolved in ethylene carbonate: dimethyl carbonate: diethyl carbonate in a ratio of 1:1:1 (EC: DMC: DEC). The electrode sheets obtained above were assembled in an anhydrous and oxygen-free glove box. The first cycle of charge and discharge was tested at a current density of 100 mA / g, and the maximum current density was 1000 mA / g for testing. The test was performed at 100 mA / g for 80 cycles, and Table 2 was obtained, wherein the 500 mAh / g charging capacity retention rate = (500 mAh / g first cycle charging capacity) / (100 mAh / g first cycle charging capacity) × 100%, and the 100 mA / g cycle 80 cycle capacity retention rate = 80th week specific capacity / 2nd week specific capacity × 100%.

[0092] The 100mAh / g cycle 80-week trend diagram of the battery obtained in Example 1-3 and Comparative Example 1-2 is as follows: Figure 6 As shown, it can be seen that the specific capacity and cycle performance of the negative electrode active materials of Examples 1-3 of the present application have obvious advantages over those of the comparative example.

[0093] Table 2

[0094]

[0095] It can be seen from Table 2 that the composite of molybdenum disulfide and graphene provided by the present invention is used as the negative electrode active material of the lithium ion battery, which can show higher specific capacity and rate performance.

[0096] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0097] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A negative electrode active material, characterized in that: The negative electrode active material comprises porous graphene and molybdenum disulfide supported on the porous graphene, and the specific surface area of ​​the negative electrode active material is 600 m 2 / g-1800m 2 / g.

2. The negative electrode active material according to claim 1, characterized in that The specific surface area of ​​the negative electrode active material is 800 m 2 / g-1200m 2 / g.

3. The negative electrode active material according to claim 1 or 2, characterized in that: The mass ratio of the porous graphene to the molybdenum disulfide is (1-2): (1-2); and / or, The molybdenum disulfide is a two-dimensional layered structure with 3 to 15 layers.

4. A method for preparing the negative electrode active material according to any one of claims 1 to 3, characterized in that: include: Providing a substrate, wherein the porosity of the substrate is 70%-95%; Generating graphene on the substrate by chemical vapor deposition to obtain graphene containing the substrate material; Adding glue to the graphene containing the substrate material, spreading the glue, and drying the graphene so that at least part of the gaps in the graphene are filled with the filling glue to obtain a first intermediate; Removing the substrate material from the intermediate, and placing the intermediate in an aqueous solution containing a soluble molybdenum source and a soluble sulfur source for hydrothermal reaction to obtain a second intermediate; The filler is removed to obtain the negative electrode active material.

5. The method according to claim 4, characterized in that The porosity of the substrate is 85%-95%; and / or, The substrate comprises at least one of foamed nickel, foamed molybdenum and foamed copper; and / or, Before depositing the graphene, the substrate is first processed by the following method: The substrate is cleaned with ketone, alcohol, acid and water in sequence, annealed at 600° C.-1200° C. for 20 min-60 min in a hydrogen and argon atmosphere, and cooled.

6. The method according to claim 4 or 5, characterized in that: The glue comprises a polymer and a solvent, wherein the mass ratio of the polymer to the solvent is 1:(10-30), preferably 1:(15-25); and / or, The polymer comprises at least one of polymethyl methacrylate, methyl methacrylate-styrene copolymer, and styrene-methacrylic acid copolymer; and / or, The solvent includes anisole.

7. The method according to claim 4 or 5, characterized in that: soaking the intermediate in hydrochloric acid to remove the substrate material in the intermediate; and / or, The temperature of the hydrothermal reaction is 120°C-200°C, preferably 150°C-180°C; and / or, The hydrothermal reaction time is 6h-18h, preferably 8h-16h; and / or, The molybdenum source includes sodium molybdate. In the aqueous solution containing the soluble molybdenum source and the soluble sulfur source, the concentration of sodium molybdate is 0.5g / L-4.0g / L, preferably 1.0g / L-3.0g / L.

8. The method according to claim 4 or 5, characterized in that: Removing the filler to obtain a negative electrode active material includes: The second intermediate is immersed in acetone for 20 min to 60 min, and freeze-dried to obtain a negative electrode active material.

9. A negative electrode plate, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 1 to 3, or the negative electrode active material prepared by the method according to any one of claims 4 to 8.

10. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 9.